SISTEM PEMBIAYAAN KEPEMILIKAN RUMAH PADA BANK KONVENSIONAL DAN SYARIAH - Dirnayanti Dirnayanti; Munadi Idris; Suhrah Suhrah (Jurnal Ekonomi Bisnis Syariah, 2020)
The home ownership financing system used by Bank BNI Syariah KCP Mikro Kolaka and BNI KCP Kolaka is generally the same financing system, because it has its own value from the community. And from each side, the Bank has several approaches to customers where the Islamic Bank approach is religious because it is a banking financial institution whose operations and products are developed based on the Qur'an and hadith. The formulation of the problem in this research is how is the Home Ownership Financing System at BNI KCP Kolaka and BNI Syariah KCP Mikro Kolaka?, What is the difference between the Home Ownership Financing System at BNI KCP Kolaka and BNI Syariah KCP Mikro Kolaka? and What are the implications of different Financing Systems for customers? The purpose of the study was to determine the Home Ownership Financing System at BNI KCP Kolaka and BNI Syariah KCP Mikro Kolaka, to find out the differences in the Home Ownership Financing System at BNI KCP Kolaka and BNI Syariah KCP Mikro Kolaka and to find out the implications of the differences in the Financing System for customers. The research method used is descriptive research with a qualitative approach with the subject of the Home Ownership Financing System in Conventional and Islamic Banks. Then the research procedures carried out include intensive observations (observations, documentation, and interviews) about the Home Ownership Financing System in Conventional and Islamic Banks. The research instruments are in the form of observation sheets or notebooks, interview guides, voice recorders, documentation sheets, photographs and required documents. The results showed that the Home Ownership Financing System in Conventional and Islamic Banks. It has several differences, namely in terms of contracts, installment calculations and the interest system because conventional banks use an interest system while Islamic banks only use a buying and selling system (murabahah).